Verb Inflection in English and Arabic: A Contrastive Analysis Study - Medjedoub, Rima (Milev Journal of Research and Studies, 2022)
Inflection, the change of word form to mark grammatical distinctions, occurs in a variety of grammatical classes: nouns, verbs, adjectives, pronouns, etc. The purpose of the present paper is to describe the verb inflectional morphology in English and Arabic and to conduct a contrastive analysis of both of them. The research question which is put forth is: how do the verb inflectional morphology in English and Arabic differ from/resemble each other? To answer this question, a systematic descriptive comparative study is carried out with a unique focus on the verb inflectional categories. Eventually, it was found that the Arabic verb inflectional morphology is richer and varied from that of the English. Such a study has implications in fields like foreign language teaching/learning, translation, electronic dictionaries, natural language processing, and the like.